(untitled) (Journal of Social Sciences Review, 2025)
This paper explored how France has reacted to this move by exclusion to AUKUS not through a direct military confrontation, but through soft balancing and hedging approaches. These included diplomatic outreach, defense co-operation, and diversification of the economy with regional powers such as India, Japan, and ASEAN members. The qualitative research approach is employed to identify official reports, policy reports, and academic sources to describe the identified behaviors of France as the outcome of the assessment of the strategic threats and an effort to maintain the status of influence in the problematic region. The study focuses on the multidimensionality of the objectives of France in balancing-seeking, the significance of norms, multilateralism, and sovereignty. France counters the ambitious nature of China to stabilize the situation in the region in a non-confrontational manner. France considers itself the major security guarantor in the Indo-Pacific. Even at the expense of AUKUS and thus, it is a key contributor to alliances without compromising their own independent status, even after AUKUS.